Natural Dye Plants for Traditional Weaving in Sintang and Sambas Regencies, West Kalimantan: TUMBUHAN PEWARNA ALAMI UNTUK TENUN TRADISIONAL DI KABUPATEN SINTANG DAN KABUPATEN SAMBAS KALIMANTAN BARAT - Muflihati; Wahdina; Kartikawati, Siti Masitoh; Wulandari, Reine Suci (Media Konservasi, 2019)
This research aimed to study natural dye plants used by Sambas and Sintang traditional weavers in West Kalimantan, Indonesia. The study includes the kinds of plants used for natural dyes and it’s existence in people’s settlements. Weavers in Sintang and Sambas Regencies of West Kalimantan Province have been using natural dye plants gathered from the forests nearby. However, forest degradation and conversion have reduced their existence. As a consequence, people begin to lose their natural dye resources. Besides, weavers use synthetic dyes because it is cheaper and more practical. Nowadays the trend ‘back to nature’ makes natural dye plants more valuable and reconsidered. The use of dye plants in traditional weaving adds their unique and inherent value, especially in the international market. An ethnobotanical methodology of a semi-structured interview was carried out to study the dye plants used in Sambas and Sintang’s traditional weaving to provide sustainable, eco-friendly dyes. The specific respondents were chosen using the Snowball Sampling Technique. The results showed that Sambas and Sintang weavers used 30 and 11 species, respectively, as dye plants. A total of 36 species were used for Sambas and Sintang traditional weaving, five of which were used as natural dye both in Sintang and Sambas. The Important Value Index of the dye plants in the field varied from high to low, and a few plants did not exist in the resident vicinity. Engkerebang (Psychotria megacoma), emarek (Symplocos ophirensis), lengkar (Litsea angulata), belian (Eusideroxylon zwageri), and kayu kuning (Fibraurea chloroleuca) are considered as native dye plants from West Kalimantan that are important to be conserved. Keywords: dye plants, ethnobotany, plant inventory, traditional weaving